Avaliação do programa mais médicos: articulando desafios, avanços e percepções na atenção primária à saúde de Itapiúna/Ceará - Freitas, Antônio Alberto (2023)
This paper evaluted of the "Mais Médicos" Program (PMM) in the municipality of Itapiúna/Ceará from the perspective of physicians and management professionals. The specific goals were: to comprehend the reflection of the experience of "Mais Médicos" Program doctors for the process of medical formation in the context of Primary Care to the Health of Itapiúna/Ceará; to identify, from the perceptions of doctors and management professionals, notes on the infrastructure "Mais Médicos" Program professionals have at disposal at Basic Health Units of Itapiúna/Ceará; and to analyze, alongside the medics and administration professionals, potential factors of valorization, fixation, and challenges in the Primary Care spaces to Health contemplated by "Mais Médicos" Program, in Itapiúna/Ceará. Evaluative Research was adopted as the theoretical-methodological perspective, based on Silva (2013), guiding a systematic application of research procedures. An evaluative methodology of qualitative nature, categorized as explicative and descriptive, was utilized. For the production of data and information, field research was done, taking as references the Basic Health Units of Caio Prado, Itans, and Palmatória, in the ambit of the Municipal Secretary of Health (SMS) of Itapiúna/Ceará. The approach to the field occurred between December 2022 and March 2023, after the Research Ethics Committee of the Federal University of Ceará (CEP/UFC/PROPESQ). Medics in activity in the PMM and management professionals that constitute the SMS of the city in focus were approached, as research subjects, with the aid of two semi-structured interview scripts. The case study was adopted as the methodological investigation approach. The bibliographic and documentary research techniques were yet used as procedures and instruments. This evaluative research rooted its orientation in the Content Analysis of Bardin (2016) to treat the collected information. Based on the analyses, the research indicated in the 'Medical Supply' category demonstrated that the health administration in Itapiúna/Ceará finds the "Mais Médicos" Program an efficient way to maintain and embrace the region's physicians, being such embracement also translated in the interest of the doctors in the experience of living the referred Program. It was observed, in the 'Primary Care Infrastructure' category, a demand for more significant investments and priority in allocating resources within the scope of Basic Care to combat the health units' precariousness and materialize the right to health of the most vulnerable social segments. The stimulation of continuous, in the 'Medical Training' category, implemented as one of the strategies linked to the PMM, was also verified. Therefore, it is a model that stimulates the enhancement of professional profile, reflecting on subjects' adherence to the "Mais Médicos" Program, which promotes the continuous formation of the medical category, fortifying SUS more and more.